1998
DOI: 10.1353/hpu.2010.0291
|View full text |Cite
|
Sign up to set email alerts
|

Peer Counseling in a Culturally Specific Adolescent Pregnancy Prevention Program

Abstract: This study evaluated the effects of peer counseling in a culturally specific adolescent pregnancy prevention program for African American females. A random pretest and multiple posttest experimental and comparison group design was used to obtain data on a sample of 63 female African American adolescents, ages 12 to 16, who lived in four public housing developments. Descriptive data and tests of significance revealed that none of the participants who received peer counseling became pregnant within three months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
67
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 32 publications
0
67
0
1
Order By: Relevance
“…Mean participant ages for individual trials ranged from 11.3 [95] to 19.3 y [75], with a median of 14.0 y across trials. Twenty-nine trials enrolled primarily minority participants [6270,73,74,76–84,8891,93,95,96,98,99], and 18 indicated that participants were of lower socioeconomic status than the general population [6265,70,73,74,7779,84,8891,95,96,99]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean participant ages for individual trials ranged from 11.3 [95] to 19.3 y [75], with a median of 14.0 y across trials. Twenty-nine trials enrolled primarily minority participants [6270,73,74,76–84,8891,93,95,96,98,99], and 18 indicated that participants were of lower socioeconomic status than the general population [6265,70,73,74,7779,84,8891,95,96,99]. …”
Section: Resultsmentioning
confidence: 99%
“…The majority of programs were school-based (ten programs [65,6769,75,83,84,87,99,100]) or community-based (24 programs [6264,70,71,73,74,76–82,85,86,8995,98]), and all but three interventions [66,72,96] took place in group settings. Pregnancy prevention was emphasised along with HIV prevention in 15 programs [62,65,6769,72,74,83–90]; the remaining programs targeted HIV only. Exposure ranged from 30 min [66] to 2,250 program hours over 3 y [89] (median exposure = approximately 10.5 h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have suggested some benefits of peer education interventions: lower cost in terms of professional staff (Milburn, 1995); demonstrated advantage of reliance of youth on peers for a variety of supports, including sexual information (Sloane & Zimmer, 1993); the role of peer educators acting as role models for healthy behaviors (Turner & Shepherd, 1999); and the opportunity for volunteers to experience personal growth and perhaps career development (Milburn, 1995;Sloane & Zimmer, 1993;Turner & Shepherd, 1999). Peer educators have been trained to reach specific target populations in healthcare (Quirk, Godkin, Schwenzteier, 1993) and other settings (Ferguson, 1998;Kelly et al, 1992;Stevens, 1994;Turner & Shepherd, 1999). Because a significant proportion of young people are increasingly enrolled in higher education, peer education is particularly appealing in this setting.…”
mentioning
confidence: 99%
“…Based on the demonstrated efficacy of peer counseling or education in many applications in health education (Devilly, Sorbello, Eccleston, & Ward, 2005;Ferguson, 1998;Klepp, Halper, & Perry, 1986;Morrow et al, 1999;Schafer, Vogel, Viegas, & Hausafus, 1998), peer education was selected as the best method to provide complex information about sources of lead and ways to protect children from exposure.…”
mentioning
confidence: 99%